Hydrothermal carbonisation of sewage sludge for char production with different waste biomass: Effects of reaction temperature and energy recycling. (15th May 2017) - Zhai, Yunbo; Peng, Chuan; Xu, Bibo; Wang, Tengfei; Li, Caiting; Zeng, Guangming; Zhu, Yun
Abstract: Hydrothermal carbonisation (HTC) of sewage sludge (SS) with waste biomass was investigated as a clean and energy-efficient treatment to produce char. The effects of the reaction temperature on the properties, composition, and energy consumption of the obtained char were investigated to evaluate the feasibility of the production process. The results indicate that the dewaterability of char derived from SS with biomass was enhanced by approximately 50% at temperatures exceeding 260 °C. The lowest moisture content of the char was 41.39%, produced from SS with cornstalk at 300 °C and holding time of 60 min. The values of H/C and O/C in char from SS with sawdust, corncob and rape straw at 300 °C dropped to approximately 0.92 and 0.04, respectively, which are close to the values of bituminous coal. SS mixed with corncob was more efficient than other biomass waste during the HTC process. The suggested optimum condition to produce char is 300 °C for 60 min, in which the HHV and energy recovery rate can reach 21.31 MJ/kg and 71.60%, respectively. As regards other types of biomass, a moderate reaction temperature above 260 °C is suggested to produce chars with an energy recovery rate ranging from 47.06% to 71.60%. Highlights: The efficient treatment for sewage sludge and waste biomass is presented. HTC reaction temperature increasing influences insignificantly the maximum of the energy recovery rate. Waste biomass improves significantly the energy recovery rate during the HTC process in a certain temperature. The performance comparison of the sewage sludge with mixed waste biomass is made.